Răspuns :
{3 * [15 + (7 + x) : 4] + 27} : 9 - 5 = 4
{3 * [15 + (7 + x) : 4] + 27} : 9 = 4 + 5
3 * [15 + (7 +x) : 4] + 27 = 9 * 9
3 * [15 + (7 + x) : 4] = 81 - 27
15 + (7 + x) : 4 = 54 : 3
(7 + x) : 4 = 18 - 15
(7 + x) : 4 = 3
7 + x = 3 * 4
7 + x = 12
x = 12 - 7
x = 5
{3 * [15 + (7 + x) : 4] + 27} : 9 = 4 + 5
3 * [15 + (7 +x) : 4] + 27 = 9 * 9
3 * [15 + (7 + x) : 4] = 81 - 27
15 + (7 + x) : 4 = 54 : 3
(7 + x) : 4 = 18 - 15
(7 + x) : 4 = 3
7 + x = 3 * 4
7 + x = 12
x = 12 - 7
x = 5
{3 * [15 + (7 + x) : 4] + 27} : 9 - 5 = 4
{3 * [15 + (7 + x) : 4] + 27} : 9 = 4 + 5
3 * [15 + (7 +x) : 4] + 27 = 9 * 9
3 * [15 + (7 + x) : 4] = 81 - 27
15 + (7 + x) : 4 = 54 : 3
(7 + x) : 4 = 18 - 15
(7 + x) : 4 = 3
7 + x = 3 * 4
7 + x = 12
x = 12 - 7= x=5
Sper ca ti-am fost de ajutor!
{3 * [15 + (7 + x) : 4] + 27} : 9 = 4 + 5
3 * [15 + (7 +x) : 4] + 27 = 9 * 9
3 * [15 + (7 + x) : 4] = 81 - 27
15 + (7 + x) : 4 = 54 : 3
(7 + x) : 4 = 18 - 15
(7 + x) : 4 = 3
7 + x = 3 * 4
7 + x = 12
x = 12 - 7= x=5
Sper ca ti-am fost de ajutor!